The Rule of Contextual Teaching and Learning Approach with Problem Solving Method to Students’ Critical Thinking Skills on Physics Chapter Work and Energy - Munadhirotul Azizah; Winarti Winarti (Jurnal Pembelajaran Fisika, 2020)
The purpose of this study was to find out: (1) the influence of Contextual Teaching and Learning (CTL) approach with a problem-solving method to students’ critical thinking skills on physics chapter work and energy, (2) the obtained improvement of students’ critical thinking skills taught using CTL approach with a problem-solving method on physics chapter work and energy. This research was a quasi-experimental study with a nonequivalent control group design. The data collection technique used was technical tests and non-tests. The data analysis technique used was description analysis and parametric statistics with t-test and Normalized Gain (N-gain). The results of this study showed that: (1) the CTL approach with problem-solving method had influenced students’ critical thinking skills and self-regulation on physics chapter work and energy with a significance level (sig. 2-tailed) of 0.025. This value obtained got smaller value than the significance value < α = 0.05. It could be said that Ha was accepted and H0 was rejected, (2) the CTL approach with problem-solving method could improve students’ critical thinking skills on physics chapter work and energy with 0.603 of N-gain score (in the medium category). Whereas the self-regulation skills based on students’ experience revealed an increased metacognition aspect as obtained by the description of students’ answers.Keywords: Contextual teaching and learning approach, a problem-solving method, critical thinking skills, self-regulation, physics chapter work, and energy.DOI: http://dx.doi.org/10.23960/jpf.v8.n1.202008